Schumpeterian Restructuring - Patrick Francois; Huw Lloyd-Ellis (Queen's University, Department of Economics, 2005)
We develop a Shumpeterian theory of business cycles that relates job creation, job destruction and wages over the cycle to the processes of firm restructuring, innovation and implementation that drive long-run growth. Due to incentive problems, production workers are employed via relational contracts and experience involuntary unemployment. Job destruction and firm turnover are counter-cyclical, but labour productivity growth and job creation are pro-cyclical. Endogenous fluctuations in job creation on the intensive margin are the dominant source of changes in employment growth. Our framework also highlights the counter-cyclical forces on wages due to restructuring, and illustrates the relationship between the cyclicality of wages and long-run productivity growth. 052
Keywords: E0; E3; O3; O4; 330; Intrinsic business cycles; job creation and destruction; innovation; wage cyclicality